Introduction of the marketplace channel under logistics service sharing in an e-commerce platform. (January 2022) - Zhang, Chuan; Ma, Hui-Min
Highlights: The interaction between the channel structure and logistics mode is studied. The conditions for both firms to agree on adding the marketplace channel are obtained. The logistics service affects consumer purchase behavior more than price. The supplier is always willing to add the channel and undertake logistics. The platform and the supplier can realize a win–win situation in some case. Abstract: In online retailing, in addition to the reseller channel, the marketplace channel has been favored by many e-commerce platforms and suppliers. Different from the reseller channel, the novel channel enables suppliers to obtain the pricing power of products and to have direct contact with consumers. However, due to the operation inefficiency of suppliers and the competition caused by adding a new channel, for suppliers and platforms, decisions on the establishment of the marketplace channel are more complex. In addition, logistics service, which affects the purchase behavior of online consumers and is considered the key to the success of online retailing, can be undertaken by both suppliers and platforms. Based on these considerations, this paper explores whether the supplier and the platform can come to an agreement on introducing the marketplace channel by incorporating the logistics service strategy. We find that compared with the product sales price, the level of logistics service has a stronger impact on the consumers' channel choice. A scenario we term RE - M S (the marketplace channel is established, and the platform and the supplier serve as the logistics providers in the reseller and the marketplace channels, respectively) produces the highest level of logistics service in the reseller channel, and a scenario termed RS - M S (the marketplace channel is established, and the supplier serves as the logistics provider in both channels) generates the highest level of logistics service in the marketplace channel. The supplier is always willing to add the marketplace channel and undertake logistics business in the marketplace channel. However, for the platform, adding the marketplace channel is advantageous only when the logistics service effectiveness or the commission rate is high. Additionally, when the supplier and the platform reach a consensus on the establishment of the marketplace channel, the RE - M S strategy can realize a win–win situation.